Perfectly vertical surface grating couplers using subwavelength engineering for increased feature sizes. - Kamandar Dezfouli, Mohsen; Grinberg, Yuri; Melati, Daniele; Cheben, Pavel; Schmid, Jens H.; Sánchez-Postigo, Alejandro; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Cheriton, Ross; Janz, Siegfried; Xu, Dan-Xia; Schmid, Jens H. (Optica, 2020)
We present perfectly vertical grating couplers for the 220 nm silicon-on-insulator platform incorporating subwavelength metamaterials to increase the minimum feature sizes and achieve broadband low back-reflection. Our study reveals that devices with high coupling efficiencies are distributed over a wide region of the design space with varied back-reflections, while still maintaining minimum feature sizes larger than 100 nm and even 130 nm. Using 3D-finite-difference time-domain simulations, we demonstrate devices with broadband low back-reflection of less than -20dB over more than 100 nm bandwidth centered around the C-band. Coupling efficiencies of 72% and 67% are achieved for minimum feature sizes of 106 nm and 130 nm, respectively. These gratings are also more fabrication tolerant compared to similar designs not using metamaterials.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/13362
Keywords: Fotónica; Óptica; Optoelectrónica; Subwavelength grating metamaterials; Surface grating couplers; Silicon photonics